Cultivation of Pleurotus eryngii (DC. ex FR.) Quel. on Agricultural Wastes - Akyuz, Mehmet (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
This study investigated the possible use of local agricultural wastes for the cultivation of Pleurotus eryngii (DC. ex Fr.) Quel. For the propagation of the main culture, 2.0 % malt extract agar (MEA) was used whereas wheat grains were used for the propagation of spawn. For the formation of basidiocarp, mixtures of wheat-cotton straw (WC), wheat-millet straw (WM) and wheat straw (W) were used as culture media. Three types of compost were prepared, consisting of a mixture of straws - W, WC (1:1) and WM (1:1). The three compost types were also supplemented with 15 % rice bran (RB). The shortest mycelium-growing period was 15 d on the average in wheat-cotton straw and the longest mycelium-growing period was 27 d in wheat-millet straw. The shortest period for the formation of primordium was 42 d on the average in wheat-cotton straw with peat soil or casing soil (CS) and the longest period was 58 d in wheat straw and in wheat-millet straw without casing soil. The longest period for the formation of the second primordium was 62 d in wheat-millet straw with casing soil. The shortest harvest period was 53 d on the average in wheat-cotton straw with casing soil, while the total harvest period was 72 d on the average in wheat-millet straw with casing soil. The highest biological efficiency (BE) was 73 % in wheat-cotton straw with casing soil, and the lowest BE was 50 % in wheatmillet straw with casing soil. The lowest average yield per 100 g of material (70 % moisture) was 15.0 g in wheat-millet straw with casing soil, while the highest yield was 22.0 g in wheat-cotton straw with casing soil. Based on the results, various local agricultural wastes can be used for the cultivation of Pleurotus eryngii.